Key Determinant Factors Towards K-Economy in Kedah - Kasmawati, Mat Japar (2005)
Knowledge and people skills accounts as the biggest assets to create wealth in this Information Age. Therefore, there is a crucial need to leapfrog from p-economy to k-economy as it promises high value added of production. As of Malaysia is at the critical moment and turning point of transition towards a k-economy country, Kedah seems to be one of the contributor to realize the Vision 2020. Therefore, Kedah initiated Kedah Maju 2010 vision. The concept of k-economy is stated as one of elements in Kedah core development strategies. However, the concept is still at defining stage in its development efforts. Therefore, this work reveals to study the current progress of Kedah Maju 2010 and thus, several initiatives are recommended due to its need to incorporate knowledge and to be competitive globally. The initiative maps strategies and action plans for leading Kedah in this new economy. It covers five thrust areas such as knowledge worker development, connectivity, electronic governance, electronic economy, and digital equity. In this regards, the initiative is then will be a reference to facilitate the state to venture in the k-economy.